Factors influencing consumer’s adoption of renewable energy - Wall, William Philip; Khalid, Bilal; Urbański, Mariusz; Kot, Michal (My University, 2021)
The objective of this study was to investigate the factors that influence the consumer adoption of renewable energy in Thailand. The study adopted an extended theory of planned behavior (TPB) by including three additional variables. The study applied a quantitative study methodology, with primary data collected using a survey of consumers in five major cities in Thailand. The data were analyzed using structural equation modeling (SEM). The findings of the study indicated that perception of self-effectiveness, environmental concern, renewable energy awareness, and beliefs about renewable energy benefits have a significant and positive effect on consumers’ intention to adopt renewable energy. The cost of renewable was found to have a negative but non-significant influence on consumers’ adoption of renewable energy, while risk/trust perception was found to have a positive but non-significant influence on consumers’ adoption of renewable energy. The study concluded that stakeholders should take into account the aspects of perception of self-effectiveness, environmental concern, renewable energy awareness, and beliefs about renewable energy benefits when running campaigns to promote the consumer adoption of renewable energy in Thailand.
Keywords: Consumers’ adoption; Environmental concern; Renewable energy; Self-effectiveness; Theory of planned behavior